Police supervisor attitudes toward organizational change - Schafer, Joseph A. (Journal of crime and justice, 2021)
Organizational change is necessary and inevitable in any organization, and is an important element of police reform. Research has demonstrated that attitudes of officers, supervisors, and administrators influence the longitudinal effectiveness of organizational change initiatives. Supervisors play a critical role in filtering messages and ensuring fidelity of initiatives at the street level. In this way, they are key actors in shaping change outcomes and their overall views of change might serve as a lynchpin for success. This study explores how previous experiences shape the attitudes of the supervisors toward the overall idea of change. Using survey data from a nationwide group of police supervisors attending the FBI National Academy program in 2009–2010, the study explores the effects of change experiences, organizational variables, and respondent demographics on views of organizational change. Results suggest that attitudes toward change align with other aspects of supervisors’ views of policing, as well as their past experiences with change efforts themselves. The findings have implications for efforts to change and reform police organizations and operations.